Características agronômicas produtivas e qualidade da silagem do sorgo forrageiro utilizando polímeros retentores de umidade no solo na entressafra agrícola - COSTA NETA, Clotilde de Morais (2023)
The objective was to evaluate the agronomic and productive characteristics and quality of forage sorghum for silage production, using polymers that retain moisture in the soil in the agricultural off-season. Two experimental tests were carried out: In the first test, an experimental design in randomized blocks (DRB) was used with four treatments represented by soil moisture retaining polymers (MRP) with different hydration intervals: control (without hydration); hydration only on the first day (1d); hydration every five days (5d); hydration every ten days (10d) and four repetitions totaling 16 experimental units. The following agronomic characteristics were evaluated: weight of the entire plant (WEP), weight of live (WL) and dead (WD) leaves, production of live (PRL) and dead (PRD) leaves, total biomass production (TBP), live and senescent leaves ratio (SLR), total biomass and live leaves ratio (TBLL). Aspects related to stem and leaf integrity were determined, such as grain color and hardness. In the second experiment, a 4x2 factorial scheme was carried out, submitting the 4 PRU treatments to two types of silage: sorghum silage exclusively and as a complete feed. Fermentative losses and chemical-bromatological composition were evaluated. Differences (P<0.05) were observed for all variables of the morphological and agronomic evaluation of forage sorghum, except for the number of dead leaves. There was an effect for Weight of dead leaves/plant and production of dead leaves with superior results for the treatments that used the MRP (0d, 5d, 10d). There was an effect (P<0.05) of interaction between the days of hydration of the MRP X CRS at the time of ensiling for gas losses (LP) and dry matter recovery (DMR) levels of the silages. Regarding the bromatological composition variables, there was an interaction effect (P<0.05) only for EE, expressed in g/Kg of DM. It is concluded from the present study that the use of moisture retaining polymers provided good results in the agronomic and productive evaluations of sorghum, with the hydrated treatment every 5 days (5d) being the most indicated according to the results.